Discharge photoelectrocatalytic system for the degradation of aromatics. (2003) - Kim, Hak-Soo; Lee, Eun-Ah; Lee, Ju-Hyeon; Han, Chul-Hee; Ha, Jin-Wook; Shul, Yong-Gun
Abstract : We have introduced the discharge photoelectrocatalytic system, in whichTiO 2 thin film coating on aluminum plate is subjected simultaneously to both UV irradiation and high voltages in excess of 3000 volts. Due to high voltagesO 3 is generated; however, efficient removal ofO 3 is observed in this photoelectrocatalytic system. In terms of the removal of volatile organic compounds (VOCs), the discharge photoelectrocatalytic system has been applied to the removal of aromatic compounds such as benzene and toluene. Based on the experimental data, the rates of the removal of these compounds in this system are higher compared to either the discharge—only system (without the photocatalyst) or the photocatalyst—only system (without high voltage discharge), and the higher rates of degradation of these compounds in the photoelectrocatalytic system are attributed to the reduced rate of electron-hole recombination inTiO 2 .